Application of valencene and prospects for its production in engineered microorganisms - Song, Yafeng; Liu, Huizhong; Quax, Wim J.; Zhang, Zhiqing; Chen, Yiwen; Yang, Ping; Cui, Yinhua; Shi, Qingshan; Xie, Xiaobao (Frontiers in Microbiology, 2024)
Valencene, a sesquiterpene with the odor of sweet and fresh citrus, is widely used in the food, beverage, flavour and fragrance industry. Valencene is traditionally obtained from citrus fruits, which possess low concentrations of this compound. In the past decades, the great market demand for valencene has attracted considerable attention from researchers to develop novel microbial cell factories for more efficient and sustainable production modes. This review initially discusses the biosynthesis of valencene in plants, and summarizes the current knowledge of the key enzyme valencene synthase in detail. In particular, we highlight the heterologous production of valencene in different hosts including bacteria, fungi, microalgae and plants, and focus on describing the engineering strategies used to improve valencene production. Finally, we propose potential engineering directions aiming to further increase the production of valencene in microorganisms.